The patient's perspective on breast radiotherapy: Initial fears and expectations versus reality. Issue 8 (26th February 2018) - Shaverdian, Narek; Wang, Xiaoyan; Hegde, John V.; Aledia, Criselda; Weidhaas, Joanne B.; Steinberg, Michael L.; McCloskey, Susan A.
Abstract : BACKGROUND: Although the efficacy and toxicity of breast radiotherapy (RT) has been studied extensively, to the authors' knowledge little is known regarding the patient's perspective on the modern breast RT experience. To better inform future patients and providers, the authors explored patient perceptions of their RT experience. METHODS: Consecutive patients who were free of disease recurrence and who had been treated between 2012 and 2016 were surveyed regarding their original fears, how short‐term and long‐term toxicities compared with initial expectations, and how pretreatment beliefs concerning RT compared with the actual experience. RESULTS: A total of 502 patients were surveyed, with a response rate of 65% (327 patients). The median patient age and posttreatment follow‐up was 59 years and 31 months, respectively. Approximately 83% of patients (269 patients) underwent breast conservation therapy. Although approximately 68% of patients (221 patients) endorsed that they initially had little to no knowledge regarding RT, approximately 47% (152 patients) reported that they had heard frightening stories. Approximately 2% of patients (6 patients) agreed that the negative stories they previously heard about RT were actually true. Approximately 92% of patients treated with breast conservation (247 patients) and 81% of patients who underwent mastectomy (47 patients) agreed with the statement "If future patients knew the real truth about RT, they would be less scared about treatment." Approximately 83% (272 patients) and 84% (274 patients), respectively, of all patients reported the overall severity of short‐term and long‐term side effects to be better than or as expected. CONCLUSIONS: Breast RT is associated with misconceptions and fears. Patients' experiences with modern breast RT appear to be superior to expectations, and the majority of patients in the current study agreed that their initial negative impressions were unfounded. Cancer 2018;124:1673‐81 . © 2018 American Cancer Society Abstract : Radiotherapy (RT) for breast cancer is associated with significant baseline fears and misconceptions that influence treatment decision making. However, herein, the majority of patients with breast cancer share that their actual experience regarding breast RT and toxicity was superior to original expectations and that baseline negative impressions were unfounded. The patients also suggest that if future patients knew the "real truth" about breast RT, they would be less scared about potential treatment.